2008
DOI: 10.1159/000151514
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Multiple Sclerosis in the Middle East

Abstract: Background: The prevalence of multiple sclerosis (MS) in the Middle East has been reported to be low to medium. Methods: To verify this assertion we conducted a review of published data on the occurrence of MS in the Middle East.Results: Fourteen studies reporting on the prevalence of MS in the Middle East were initially identified, 5 of which were excluded due to inadequate data or serious methodological limitations. The data from the 9 included studies suggested that the prevalence of MS may vary widely with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 82 publications
1
15
1
Order By: Relevance
“…Our finding of an overall prevalence rate of 55.98/ 100,000 population is higher than that of the last report from Iran [12] and is the highest rate ever reported from the Middle-East countries except Israel [7] .…”
Section: Discussioncontrasting
confidence: 74%
“…Our finding of an overall prevalence rate of 55.98/ 100,000 population is higher than that of the last report from Iran [12] and is the highest rate ever reported from the Middle-East countries except Israel [7] .…”
Section: Discussioncontrasting
confidence: 74%
“…However, we cannot draw a definite conclusion about the prevalence of MS in Middle-Eastern countries due to methodological inconsistencies among published studies. Nevertheless, we can conclude that the prevalence in those countries is escalating, and it depends on the specific population and environment of the study [28].…”
Section: Discussionmentioning
confidence: 83%
“…In Kuwait the reported crude prevalence has increased from 10/100,000 in 1980 [26] to 14.7/100,000 in 2000 [27]. The prevalence among a pure Kuwaitis population was 11.02/100,000 in 1993 and increased to 31.15/100,000 in 2000 [28]. The reported prevalence in Jordan was 7/100,000 [29] but recently it has been reported to be 32/100,000 in one study [30] and 39 per 100,000 in another [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, Al-Hashel et al published a paper in 2008 about the epidemiology of MS in the Middle East, including Syria [7]. They concluded that it was difficult to draw any definite conclusions regarding the prevalence of MS in the Middle East due to methodological inconsistencies in published studies.…”
Section: Ms In Syriamentioning
confidence: 99%
“…A substantial increase in MS incidence has been reported from different countries within the Levant region [3][4][5][6][7]. If such an increase reflects a real change in incidence, it can reasonably be attributed to environmental factors since population genetics shapes the disease at a much slower rate.…”
Section: Is Ms In the Levant Increasing?mentioning
confidence: 99%